Factors Influencing Omni-Channel Experience and Its Impact on Brand Love and Customer Loyalty - Audi Putranto Butar Butar; Unggul Kustiawan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study focuses on the Omnichannel Strategy, which is necessary to enhance brand love and its impact on customer loyalty in fulfilling consumer satisfaction with the experience of purchasing food at Padang restaurants. The purpose of this study is to determine the influence of channel service configuration, integrated interaction, and customer empowerment on the omni-channel experience; to analyze the effect of the omni-channel experience on brand love; and to analyze the effect of brand love on customer loyalty. This research serves as a development of previous similar studies that have not extensively explained the research object of online market customers who purchase Padang food through online markets in Tangerang. The contribution of this study is expected to provide information at both the theoretical level of marketing management and in practical marketing strategies that have a positive impact on consumers as well as the consumers studied. Data collection in this study was conducted using a survey method, in which questionnaires were distributed online. Respondents were selected using a purposive sampling method targeting Padang restaurant customers who purchased Padang dishes through GoFood in Tangerang. For the analysis, the Variance-Based Structural Equation Modeling (PLS-SEM) method was employed using the SmartPLS application. The results of this study have proven a positive influence between channel service configuration, integrated interaction, and customer empowerment on the omni-channel experience. Furthermore, the omni-channel experience was also found to affect brand love, and ultimately, brand love influences both behavioral loyalty and attitudinal loyalty. Keywords – Attitudinal Loyalty, Behavioral Loyalty, Brand Love, Channel Service Configuration, Customer Empowerment, Integrated Interaction, Omnichannel Experience